Insights into strength and deformation in Al-doped Ti3SiC2 MAX phase after irradiation with a mixed spectrum of high-energy protons and spallation neutrons - Peng Song; Zhiguang Wang; Tielong Shen; Yushan Yang; Jianrong Sun; Sosuke Kondo; Yong Dai (Journal of Materials Research and Technology)
An Al-doped Ti3SiC2 MAX phase containing dual phases α-Ti3SiC2 and α-Al2O3 grains was irradiated at around 125 °C in Target-10 of the Swiss spallation neutron source (SINQ) under a mixed spectrum of high-energy protons and spallation neutrons to approximately 8.4 displacements per atom (dpa), 575 appm helium and 1350 appm hydrogen. The microstructures, strength and deformation mechanisms of both irradiated and unirradiated Al-doped Ti3SiC2 were investigated using the transmission electron microscopy (TEM), nanoindentation and micropillar compression. After irradiation, high-density defect clusters and dislocation loops were formed in α-Ti3SiC2 grains, and the resistance against microcracking was enhanced. As a result, the strength of the Al-doped Ti3SiC2 under micropillar compression was increased from 1.9 ± 0.1 to 6.1 ± 0.6 GPa, although the E modulus was almost unchanged. Regardless of irradiation, this material showed brittle fracture with virtually no plastic deformation under micropillar compression. TEM observations of the deformed regions underneath Vickers indentation revealed microcracks parallel to the {0 0 0 1} basal planes in the unirradiated specimen and defect-free dislocation channels parallel to the {1 1 0 1} planes in the irradiated specimen. This suggests that the slip systems in the Al-doped Ti3SiC2 are similar to those of hcp Zr alloys, namely prismatic {−1101} and basal {0001} slip planes and dislocation channeling is a deformation mechanism in the irradiated Al-doped Ti3SiC2 phase.